What do europeans believe to be the causes of poverty? A multilevel analysis of heterogeneity within and between countries - Costa, L. P.; Dias, J. G. (Social Indicators Research, 2015)
People’s explanations for why some individuals are poor are of great importance to a comprehensive study of poverty. This cross-cultural study aims to profile differences and similarities in perceptions of the causes of poverty within and between 28 European Union countries. Multilevel models were estimated to allow two levels of analysis to be studied simultaneously, namely the individual and the country, and a multilevel latent class model was selected with six classes of countries and seven classes of individuals. Despite the generalization of the social explanations of poverty at the individual level, some groups also blame the poor for their situation. Individuals in greater economic difficulty attributed more social causes to poverty than those who were better off financially and socially. At the country level, the most developed countries believe poverty has individualistic and fatalistic causes, whereas the least developed countries explain poverty based on the injustices of society. We found that this methodology permits a deeper and richer analysis than traditional clustering methods as it accounts for different nested levels of analysis simultaneously.